EVALUATION OF MECHANICAL RESISTANCE BY THE FINITE ELEMENTS METHOD OF A MACHINING TOOL WITH INTERNAL COOLING CHANNELS - França, P. H. P.; da Silva, L. R. R. (Revista de Engenharia Térmica, 2021)
In this work, the strength of machining hardware for the modified turning process with internal channels that circulates water as a coolant through a closed system was studied. As output parameters, the mechanical strength at the cutting edge and in the grooves was studied. In addition, input parameters were considered different force and thermal flow conditions generated in the tool's cutting edge. All analyzes performed: Influence of temperature on tool stress, comparison of the maximum stresses in the tool channels with the cutting edge, and the influence of coolant stress in the internal channels were performed using the finite element method by the Ansys® Workbench software 19.2. The main conclusions were that the parameter that most influences the tension exerted on the tools is the force and that, according to the force exerted, the tool will not resist the tension efforts.